Changes in task-specific fear of movement and impaired trunk motor control by pain neuroscience education and exercise: A preliminary single-case study of a worker with low back pain. (October 2022) - Fujii, Ren; Imai, Ryota; Shigetoh, Hayato; Tanaka, Shinichiro; Morioka, Shu
We report a case (a worker with low back pain) who was provided patient education and therapeutic exercise, and we performed a detailed kinematic analysis of his work-related activity over time. The subjects were one 28-year-old male worker with low back pain. In addition, to clearly identify impaired trunk movement during work-related activity in the low back pain subject, 20 age-matched healthy males (control group) were also included as a comparison subject. He received pain neurophysiology education and exercise instruction. We analyzed the subject's trunk movement pattern during a lifting task examined by a three-dimensional–motion capture system. In addition, task-specific fear that occurred during the task was assessed by the numerical rating scale. The assessment was performed at the baseline phase (4 data points), the intervention phase (8 data points), and the follow-up phase (8 data points), and finally at 3 and 8 months after the follow-up phase. No intervention was performed in the control group; they underwent only one kinematic evaluation at baseline. As a result, compared to the control group, the low back pain subject had slower trunk movement velocity (peak trunk flexion velocity = 50.21 deg/s, extension velocity = −47.61 deg/s), and his upper-lower trunk segments indicated an in-phase motion pattern (mean absolute relative phase = 15.59 deg) at baseline. The interventions reduced his pain intensity, fear of movement, and low back pain–related disability; in addition, his trunk velocity was increased (peak trunk flexion velocity = 82.89 deg/s, extension velocity = −77.17 deg/s). However, the in-phase motion pattern of his trunk motor control remained unchanged (mean absolute relative phase = 16.00 deg). At 8 months after the end of the follow-up, the subject's in-phase motion pattern remained (mean absolute relative phase = 13.34 deg) and his pain intensity had increased. This report suggests that if impaired trunk motor control remains unchanged after intervention, as in the course of the low back pain subject, it may eventually be related to a recurrence of low back pain symptoms.